Adjuvant radiotherapy for stage pN1M0 esophageal squamous cell carcinoma: Results from a Chinese two‐center study. Issue 6 (17th May 2019) - Ni, Wenjie; Chen, Junqiang; Xiao, Zefen; Yu, Shufei; Zhang, Wencheng; Zhou, Zongmei; Chen, Dongfu; Feng, Qinfu; Chen, Xiaohui; Lin, Yu; Zhu, Kunshou; Gao, Shugeng; et al.
Abstract : Background: Whether postoperative radiotherapy is beneficial in the treatment of esophageal squamous cell carcinoma with one or two regional lymph node (LN) metastases (pN1) after esophagectomy is uncertain. This study aimed to explore the effect of postoperative radiotherapy (PORT) on survival. Methods: Propensity score‐matching (PSM) analysis was conducted to balance the two arms (surgery only [S] or surgery plus postoperative radiotherapy [PORT]). The survival rate was calculated by the Kaplan‐Meier method and analyzed using the log‐rank test. Results: A total of 992 cases confirmed positive for one or two regional LN metastases were eligible. After PSM, 622 patients were reviewed. Each group consisted of 311 cases. The median follow‐up was 80.7 months. For the overall cohort, the one‐, three‐ and five‐year overall survival (OS) were 90.6%, 51.9% and 38.2%, respectively. Disease‐free survival (DFS) was 76.0%, 41.4% and 32.1%, respectively. The five‐year OS and DFS were 45.0% and 39.8% for PORT, which was significantly higher than the S group (31.3% and 24.2%, both P < 0.001). On subgroup analysis, PORT was associated with improved OS and DFS for patients with pathological stage pT3–4N1M0, compared with S group (five‐year OS 41.3% vs. 23.5%, P < 0.001; five‐year DFS 35.8% vs. 18.8%, P < 0.001). However, for pT1–2N1M0 patients, PORT did not benefit OS and DFS compared with S ( P = 0.063). Conclusions: In summary, the addition of PORT after esophagectomy was associated with a statistically significant improvement in OS and DFS for patients with pathological one or two lymph‐node positive pathology, in particular for stage pT3–4N1M0 patients.